Orchestrating and coordinating scientific/engineering workflows using GridShell - Walker, E.; Minyard, T. (Proceedings of the IEEE International Symposium on High Performance Distributed Computing, 2004)
GridShell maps grid and distributed computing concepts to the UNIX shell programming environment. This allows scientific and engineering users, already familiar with Tenex C Shell (tcsh) and Bourne Again Shell (bash), to quickly use the services provided by these distributed resources. Our demo will show how the scripting capabilities of GridShell can be used to orchestrate and coordinate the workflow of an engineering simulation using an established 2D flow solver.